2022
DOI: 10.1016/j.tranon.2021.101244
|View full text |Cite
|
Sign up to set email alerts
|

FLT3 inhibition by olverembatinib (HQP1351) downregulates MCL-1 and synergizes with BCL-2 inhibitor lisaftoclax (APG-2575) in preclinical models of FLT3-ITD mutant acute myeloid leukemia

Abstract: Introduction FLT3-ITD mutations occur in approximately 25% of patients with acute myeloid leukemia (AML) and are associated with poor prognosis. Despite initial efficacy, short duration of response and high relapse rates limit clinical use of selective FLT3 inhibitors. Combination approaches with other targeted therapies may achieve better clinical outcomes. Materials and methods Anti-leukemic activity of multikinase inhibitor olverembatinib (HQP1351), al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…In these AML cells, the increased cleavage of caspase 3 and poly(ADP-ribose) polymerase (PARP) prove the enhanced apoptosis. This finding also indirectly proves that expansion of FLT3-ITD is indeed involved in the resistance of cells to venetoclax [ 67 ].…”
Section: Introductionmentioning
confidence: 67%
“…In these AML cells, the increased cleavage of caspase 3 and poly(ADP-ribose) polymerase (PARP) prove the enhanced apoptosis. This finding also indirectly proves that expansion of FLT3-ITD is indeed involved in the resistance of cells to venetoclax [ 67 ].…”
Section: Introductionmentioning
confidence: 67%
“…According to previous test methods [ 26 ], to detect early and late apoptosis, using Annexin V-FITC/PI dual staining detection kits (Beyotime, Shanghai, China). Cells(1 × 10 6 ) were stained with 5 µL of Annexin V and 10 µL of PI in 198 μL of 1× binding buffer for 15 min at room temperature in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…APG-2575 (lisaftoclax) is a BCL-2 selective inhibitor independently developed by Suzhou Ascentage Pharma, several clinical trials have been initiated in hematologic malignancies [ 13 ]. The results of the phase I trial (NCT03537482) showed that APG-2575 had anti-tumor activity and tolerable safety in patients with relapsed/refractory chronic lymphocytic leukemia (R/R CLL), small lymphocytic lymphoma (SLL) and other hematologic tumors [ 14 ].…”
Section: Introductionmentioning
confidence: 99%